L-Asparaginase production by actinomycetes isolated from some Thai medicinal plant rhizosphere soils - Khamna S. (2014)
Abstract The actinomycetes (445 strains), isolated from 16 Thai medicinal plant rhizosphere soils were examined for their L-asparaginase activity. It was found that thirty strains showed enzyme activity. The range of enzyme production was 0.03-1.50 μmol ammonia/ml/hour. Strain CMU-H002 isolated from lemongrass (Cymbopogon citratus) rhizosphere soil showed highest enzyme activity. Based on the 16S rDNA sequence analysis, this strain was most closely related to Amycolatopsis kerataniphila subsp. kerataniphila DSM 44409T (98.6% similarity) and Amycolatopsis keratiniphila subsp. nogabecina DMS 44586T (98.7% similarity). The L-asparaginase activity was maximums (3.05 μmol ammonia/ml/hour) when strain CMU-H002 was cultivated in asparagine dextrose salts broth amended with soluble starch (0.2%) and yeast extract (1.5%), pH 7.0 and incubated at 30°C with shaking at 125 rpm for 7 days. © IJIB, All rights reserved.